The Role of Moving Shocks, Unemployment, and Policy in Understanding Housing Bust - Krivenko, Pavel (Journal of Banking & Finance, 2023)
I use panel data from the Survey of Consumer Finances to study the recent U.S. housing bust in a quantitative lifecycle model. In the model, households face two types of idiosyncratic shocks: income shocks and moving shocks. The income shocks produce the large and long-lasting impact of unemployment on future earnings documented in recent empirical work. The moving shocks are estimated from survey data on reasons for moving to match the characteristics of marginal buyers. Movers are younger, have lower wealth and less secure jobs, making them more sensitive to unemployment and credit conditions. Moving shocks amplify the quantitative importance of labor and credit channels that explain the observed decline in house prices and rise in foreclosures. The Home Affordable Modification Program helped stabilize prices and reduce foreclosures at a relatively small cost, working mainly as insurance against bad shocks to the most vulnerable households.